A new species of Gonolobus (Apocynaceae) from Veracruz, Mexico - Lozada-Pérez, Lucio; Castro, Ericka Belén Cortez (Phytotaxa, 2023)
Gonolobus sanmartinus is herein described and illustrated from the state of Veracruz, Mexico. It is an endemic species to the Los Tuxtlas region and similar in foliar features to those of G. pallidus. However, the faucial ring and gynostegial corona are remarkably different. This new species shares its distribution with G. ancorifer, G. fraternus, G. niger and G. versicolor, and a dichotomous identification key for these species in the Los Tuxtlas region is included. The new species’ relationship with other species is discussed and a geographic distribution map is presented, as well as its conservation status.